A Dual‐Color Fluorescent Probe Allows Simultaneous Imaging of Main and Papain‐like Proteases of SARS‐CoV‐2‐Infected Cells for Accurate Detection and Rapid Inhibitor Screening. (14th January 2022) - Cheng, Yong; Borum, Raina M.; Clark, Alex E.; Jin, Zhicheng; Moore, Colman; Fajtová, Pavla; O'Donoghue, Anthony J.; Carlin, Aaron F.; Jokerst, Jesse V.
Abstract: The main protease (M pro ) and papain‐like protease (PL pro ) play critical roles in SARS‐CoV‐2 replication and are promising targets for antiviral inhibitors. The simultaneous visualization of M pro and PL pro is extremely valuable for SARS‐CoV‐2 detection and rapid inhibitor screening. However, such a crucial investigation has remained challenging because of the lack of suitable probes. We have now developed a dual‐color probe (3MBP5) for the simultaneous detection of M pro and PL pro by fluorescence (or Förster) resonance energy transfer (FRET). This probe produces fluorescence from both the Cy3 and Cy5 fluorophores that are cleaved by M pro and PL pro . 3MBP5‐activatable specificity was demonstrated with recombinant proteins, inhibitors, plasmid‐transfected HEK 293T cells, and SARS‐CoV‐2‐infected TMPRSS2‐Vero cells. Results from the dual‐color probe first verified the simultaneous detection and intracellular distribution of SARS‐CoV‐2 M pro and PL pro . This is a powerful tool for the simultaneous detection of different proteases with value for the rapid screening of inhibitors. Abstract : The simultaneous visualization of crucial proteases within SARS‐CoV‐2‐infected cells can be a significant benefit for the accurate detection of virus and rapid screening of inhibitors as well as for understanding the viral lifecycle. The catalytic efficiency, intracellular enzyme activity, and distribution of SARS‐CoV‐2 main protease and papain‐like protease have now been exploited using peptide‐based dual‐color FRET probes and their inhibitors.